Deteksi Kejadian Residu Tetrasiklin pada Daging Ikan Nila di Kota Yogyakarta dengan Kromatografi Cair Kinerja Tinggi (KCKT) - Wari Pawestri; Gagak Dhony Satria; Nisa Hakimah; Doddi Yudhabuntara (Jurnal Sain Veteriner, 2019)
Food products of animal origin which are free from biological and chemical contamination are an absolute requirement of food safety. Antibiotics residues in the food of animal origin is one of the chemical contaminants in food are harmful/hazardous to human health. Tetracycline is an antibiotic that is often used in the fishing industry. The study aims to detect the occurrence of tetracycline residues in tilapia sold in traditional markets in Kota Yogyakarta. The research was conducted with detection test (detect disease). The study used 61 samples of tilapia fish from 16 traditional markets in Kota Yogyakarta. Tilapia meat samples are prepared according to the Association of Official Analytical Chemistry (AOAC). The existence of tetracycline residues in meat can be detected by high performance liquid chromatography (HPLC). Residue analysis in fish meat was conducted at the Department of Pharmacology, Faculty of Veterinary Medicine of Gadjah Mada University using HPLC Shimadzu version 6.1. The results showed that 24 samples of tilapia meat marketed in Kota Yogyakarta was positively contained tetracycline antibiotic residues. A total of 19 samples contained residues above maximum residue limits (MRL). The conclusion of the study is 31% of tilapia marketed in Kota Yogyakarta contains tetracycline residues above MRL. Surveillance of residues in food of animal origin and further research in terms of reducing antibiotic residue in tilapia meat is highly recommended to improve the quality and safety of food of animal origin.